Behavioural responses of sardines Sardina pilchardus to simulated purse-seine capture and slipping - Marçalo, A. (2016)
The behavioural effects of confinement of sardine Sardina pilchardus in a purse seine were evaluated through three laboratory experiments simulating the final stages of purse seining; the process of slipping (deliberately allowing fishes to escape) and subsequent exposure to potential predators. Effects of holding time (the time S. pilchardus were held or entangled in the simulation apparatus) and S. pilchardus density were investigated. Experiment 1 compared the effect of a mild fishing stressor (20min in the net and low S. pilchardus density) with a control (fishing not simulated) while the second and third experiments compared the mild stressor with a severe stressor (40min in the net and high S. pilchardus density). In all cases, sea bass Dicentrarchus labrax were used as potential predators. Results indicated a significant effect of crowding time and density on the survival and behaviour of slipped S. pilchardus. After simulated fishing, S. pilchardus showed significant behavioural changes including lower swimming speed, closer approaches to predators and higher nearest-neighbour distances (wider school area) than controls, regardless of stressor severity. These results suggest that, in addition to the delayed and unobserved mortality caused by factors related to fishing operations, slipped pelagic fishes can suffer behavioural impairments that may increase vulnerability to predation. Possible sub-lethal effects of behavioural impairment on fitness are discussed, with suggestions on how stock assessment might be modified to account for both unobserved mortality and sub-lethal effects, and possible approaches to provide better estimates of unobserved mortality in the field are provided. (C) 2013 The Fisheries Society of the British Isles